Differential effects of N and P additions on foliar stoichiometry between species and community levels in a subtropical forest in eastern China. (October 2020) - Zheng, Zemei; Lu, Jiang; Su, Yuqin; Yang, Qingsong; Lin, Yihua; Liu, Heming; Yang, Jing; Huang, Hui; Wang, Xihua
Highlights: Nutrient addition increased foliar P in species with lower initial foliar P. The LnRR of foliar P to fertilization negatively correlated with initial foliar P. The limiting P controlled the responses of species foliar N and P to fertilization. The community foliar P response was driven by varied species-specific responses. Abstract: The responses of foliar nitrogen (N) and phosphorus (P) stoichiometry to nutrient additions are important indicators of various ecological processes, especially under climate change. However, how nutrient additions affect foliar N and P stoichiometry from species to community levels remain unclear, especially in P-limited systems. In this study, we conducted a nutrient additions experiment with control, N addition, P addition, and NP addition treatments in a P-limited subtropical forest to examine the effects of nutrient additions on foliar N and P stoichiometry. Our results showed that nutrient additions did not significantly influence foliar N concentration in seven dominant plant species over a three-year experimental period but significantly increased foliar P concentration and decreased foliar N:P ratio in species with lower initial foliar P concentration. The interactive effects of N and P additions on foliar P concentration and N:P ratio were synergistic and antagonistic, respectively. The response ratio of foliar P concentration to nutrient addition had a significantly negative correlation with initial foliar P concentration ( r = −0.644), but had a positive one with initial foliar N:P ratio ( r = 0.619). These results suggest that the limiting P dominated the responses of foliar N and P stoichiometry to nutrient additions at species level. At the community level, foliar P concentration and N:P ratio for both community weighted means (CWM) and community non-weighted means (CM) showed weaker positive responses to N and P additions than those at species level and there was no differential response between CWM and CM, suggesting the control of varied species responses on community foliar P concentration and N:P ratio response. Taken together, our results highlight the differential impacts of nutrient additions on foliar N and P stoichiometry between species and community levels, which needs to be considered in models when assessing the responses of ecosystem function to nutrient enrichments.